THE EFFECTIVENESS OF STORYTELLING TECHNIQUE IN PUBLIC SPEAKING SUBJECT OF SECOND SEMESTER - Widiani, Agnes nopita; Astriyanti, Diah; Hafis, Maliqul (IKIP PGRI Pontianak, 2024)
The Effectiveness of Storytelling Technique in Public Speaking Subject of Second Semester Students (A Pre-Experimental research at the English Education Study Program Students of IKIP PGRI Pontianak). Supervised by Dr. Diah Astriyanti, M.Pd and Maliqul Hafis, M.Pd. Language and Art University of Teacher Training and Education Institute of the Republic of Indonesia Teachers Association Universitas PGRI Pontianak 2024. This study aims to determine how well students in the second semester of public speaking employ the storytelling strategy University PGRI Pontianak. This study used pre-experimental research, in collecting the data, the researcher used the pre-test and post-test for tools of data collection with the use of test instructions of speaking. Second semester students majoring in English were population of this research with a total of 93 consisting of A Morning 26 students, B Morning 36 students, and A Afternoon 31 students. This research use cluster random sampling. A regional sampling method called cluster random sampling is used to choose samples when the subject of the study or the data source is relatively large. The researcher inspect the homogeneity sample with the same criteria and conducts the same batch, and same study program. The results of this research indicate that the storytelling method is effective and important for public speaking students. Students obtained an average score of 48.97 before the test and increased to 85.32 after using the storytelling method. Based on the table, the sig value. two tails is 0.01 and the sig value. two tails less than 0.05, which indicates that there is a significant difference between learning outcomes before and after the test. Therefore, it can be concluded that learning using the storytelling method is effective in increasing students' speaking ability scores. The alternative hypothesis (Ha) is accepted: the grades of second semester students at IKIP PGRI Pontianak change after using the storytelling method.